(untitled) (Communications in Computational Physics, 2023)
We detail some of the understudied aspects of the flow inside and around the Hexactinellid Sponge Euplectella aspergillum. By leveraging the flexibility of the Lattice Boltzmann Method, High Performance Computing simulations are performed to dissect the complex conditions corresponding to the actual environment at the bottom of the ocean, at depths between 100 and 1,000 m. These large-scale simulations unveil potential clues on the evolutionary adaptations of these deep-sea sponges in response to the surrounding fluid flow, and they open the path to future investigations at the interface between physics, engineering and biology.